(untitled) (Dhaka University Journal of Science, 2015)
Many countries devaluate their own currencies on the basis of assumption that promoting export is an important aspect in economic growth. This paper uses 25 years (1987 to 2011) panel data for 33 such countries with their major export items to empirically examine whether devaluation of these countries currency matter for change in exports for major items by using different econometrics techniques. Results find that devaluation of the currencies cause export to decrease rather than to increase. Thus countries should follow appropriate policy for currency appreciation than currency depreciation for export promotion. DOI: http://dx.doi.org/10.3329/dujs.v63i1.21769 Dhaka Univ. J. Sci. 63(1): 53-57, 2015 (January)